A COMPARATIVE STUDY ABOUT THE IMPACT OF STRESS ON JOB SATISFACTION BETWEEN JORDANIAN AND SAUDI NURSES - AbuRuz, Mohannad Eid (European Scientific Journal, ESJ, 2014)
There is accumulative evidence that stress negatively affects health care providers. Stress in nursing is increasing due to the changing nature of the profession. This stress results from internal and external sources. Stress decreases job satisfaction for the nurses resulting in numerous undesirable consequences. The purpose of this study was to identify the sources of stress for Jordanian nurses and to compare the effect of stress on job satisfaction between Jordanian and Saudi nurses. A descriptive cross-sectional correlational design was used to meet the purposes of the study. A total of 150 nurses from a private hospital in Amman Jordan and 100 nurses from a self-operated hospital in Dammam, Saudi Arabia completed the study questionnaires. The results showed that the stressful situations for Jordanian nurses were: death and dying, workload, and patients and their families. There was a significant negative relationship between stress and job satisfaction for Jordanian nurses r(148)= -0.630, pË‚.05 and for Saudi nurses r(98)= -0.437, pË‚.05. Jordanian nurses were less satisfied with their jobs compared to Saudi nurses Z = -2.09, p < .05. In conclusion, stress is a global problem for nurses and negatively affects job satisfaction. Nurse managers should take appropriate actions to decrease stress helping their nurses to work efficiently and effectively.